A review on mechanical performance of hybrid natural fiber polymer composites for structural applications - Mohd Nurazzi, Norizan; M. Asyraf, M. R.; Sabaruddin, Fatimah Athiyah; Shamsudin, Siti Shazra Shazleen; Shafi, Ayu Rafiqah; Moklis, Muhammad Harussani; Kamarudin, S. H.; Razman, M. R.; M., Rahmah; Zainudin, Edi Syams; Ilyas, R. A.; Alias, Aisyah Humaira; et al. (Multidisciplinary Digital Publishing Institute, 2021)
In the field of hybrid natural fiber polymer composites, there has been a recent surge in research and innovation for structural applications. To expand the strengths and applications of this category of materials, significant effort was put into improving their mechanical properties. Hybridization is a designed technique for fiber-reinforced composite materials that involves combining two or more fibers of different groups within a single matrix to manipulate the desired properties. They may be made from a mix of natural and synthetic fibers, synthetic and synthetic fibers, or natural fiber and carbonaceous materials. Owing to their diverse properties, hybrid natural fiber composite materials are manufactured from a variety of materials, including rubber, elastomer, metal, ceramics, glasses, and plants, which come in composite, sandwich laminate, lattice, and segmented shapes. Hybrid composites have a wide range of uses, including in aerospace interiors, naval, civil building, industrial, and sporting goods. This study intends to provide a summary of the factors that contribute to natural fiber-reinforced polymer composites’ mechanical and structural failure as well as overview the details and developments that have been achieved with the composites.